The economic effects of federalism and decentralization : a cross-country assessment - Stefan Voigt; Lorenz Blume (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper explores the idea that institutional details matter and that attempts to estimate the economic effects of federalism by employing a simple dummy variable neglect potentially important institutional details. Based on a principal component analysis, seven aspects of both federalism and decentralization are used as variables for explaining differences in (1) fiscal policy, (2) government effectiveness, (3) economic productivity, and (4) happiness. The results show that institutional details do, indeed, matter. Different aspects of federalism impact on the outcome variables to different degrees. This study adds to our knowledge on the transmission mechanisms of federalism and decentralization.
Keywords: H71; H11; 330; federalism; decentralization; fiscal federalism; economic effects of constitutions; constitutional economics; Föderalismus; Dezentralisierung; Finanzföderalismus; Verfassungsökonomik; Wirkungsanalyse; Schätzung; Welt